Peran Dan Pengaruh Media Digital Dalam Issue Pelecehan Seksual Di Indonesia - Makmur Jaya; Rita Zahara (Lembaga Pengembangan Kinerja Dosen, 2023)
The rapid growth of technology and communication has brought various influences to life in society. Increasingly sophisticated and widespread digital media has made people dependent on using the media. Where digital media is useful as a means of communication between individuals and groups. The impact on the use of media other than as a medium of communication can also cause a crime in behavior. Such as deviant behavior that can cause anxiety for society. One of them is sexual harassment which is currently increasingly prevalent and increasing on social media. The targets in social harassment are not only aimed at adults but also at children and adolescents. Sexual harassment can cause various adverse effects for victims which will result in disruption of mental and personality development both physically and psychologically. This must be balanced with caution in using the media to avoid social harassment. The use of social media must be done with supervision if children use it. In addition, social users need to be equipped with adequate knowledge and knowledge about wise attitudes and behavior when using social media so they can avoid various things that can harm themselves and others.